Review of Ptilomera (Ptilomera) (Hemiptera: Heteroptera: Gerridae) from India, with description of a new species - Jehamalar, E. Eyarin; Chandra, Kailash; Basu, Srimoyee; Selvakumar, C. (Zootaxa, 2018)
The subgenus Ptilomera (Ptilomera) Amyot & Serville, 1843 of India is reviewed and Ptilomera (P.) nagalanda Jehamalar & Chandra, sp. nov. is described from Peren District, Nagaland, India. The new species can clearly be distinguished from its congeners in India by the presence of silvery white setae on the sub-lateral region of the meso- and metanota and the presence of a fringe of fine short setae of different lengths on the flexor region of the mid femur reaching beyond the middle in the male. Detailed illustrations of the apterous male of the new species and male and female of other species of Ptilomera, except P. occidentalis Zettel, are given. Distribution maps and a key to all known species of Ptilomera (Ptilomera) in India are given.